2009
DOI: 10.1016/j.virol.2009.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Apple latent spherical virus vectors for reliable and effective virus-induced gene silencing among a broad range of plants including tobacco, tomato, Arabidopsis thaliana, cucurbits, and legumes

Abstract: Apple latent spherical virus (ALSV) vectors were evaluated for virus-induced gene silencing (VIGS) of endogenous genes among a broad range of plant species. ALSV vectors carrying partial sequences of a subunit of magnesium chelatase (SU) and phytoene desaturase (PDS) genes induced highly uniform knockout phenotypes typical of SU and PDS inhibition on model plants such as tobacco and Arabidopsis thaliana, and economically important crops such as tomato, legume, and cucurbit species. The silencing phenotypes per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
170
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(178 citation statements)
references
References 42 publications
8
170
0
Order By: Relevance
“…Our finding also implies that many other available viral vectors, such as Apple latent spherical virus (Igarashi et al, 2009;Yamagishi et al, 2011), Brome mosaic virus (Ding et al, 2006), and Barley stripe mosaic virus (Holzberg et al, 2002), could be used in a similar strategy to the TRV VbMS vector for functional analysis of miRNAs in a diverse range of eudicot and monocot crops. In addition, besides IPS1-based miRNA target mimicry and STTM methods, several other techniques, such as transcriptional gene silencing of miRNA gene promoters (Vaistij et al, 2010), artificial miRNA-directed silencing of miRNA precursors (Eamens et al, 2011), and miRNA decoy (Ivashuta et al, 2011), have successfully been used to investigate miRNA/target interactions in transgenic plants.…”
Section: Discussionmentioning
confidence: 61%
“…Our finding also implies that many other available viral vectors, such as Apple latent spherical virus (Igarashi et al, 2009;Yamagishi et al, 2011), Brome mosaic virus (Ding et al, 2006), and Barley stripe mosaic virus (Holzberg et al, 2002), could be used in a similar strategy to the TRV VbMS vector for functional analysis of miRNAs in a diverse range of eudicot and monocot crops. In addition, besides IPS1-based miRNA target mimicry and STTM methods, several other techniques, such as transcriptional gene silencing of miRNA gene promoters (Vaistij et al, 2010), artificial miRNA-directed silencing of miRNA precursors (Eamens et al, 2011), and miRNA decoy (Ivashuta et al, 2011), have successfully been used to investigate miRNA/target interactions in transgenic plants.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to the insert size and position of target genes, the effect of the cloning orientation of the foreign gene was investigated using white lupin plants. No clear differences were detected between sense and antisense orientations in this study (Figure 4), although antisense fragments have been shown to be more effective for silencing in other VIGS systems (Igarashi et al 2009;Pflieger et al 2008;Zhang et al 2010). …”
Section: Discussionmentioning
confidence: 49%
“…The results indicate that there are size constraints of insert fragments in the PSV VIGS vector and that 50-190 bp is the optimal length needed to induce silencing. The size constraints of insert fragments have also been reported in other viral vector systems, where vectors with larger inserts are more susceptible to losing the inserts within the plants (Hsieh et al 2013;Huang et al 2009;Igarashi et al 2009;Liu and Page 2008;Peele et al 2001;SenthilKumar and Mysore 2011b;Yuan et al 2011).…”
Section: Discussionmentioning
confidence: 67%
“…Most of these vectors work well in Solanaceae family, especially in tomato and N. benthamiana, but few in another economically important crop, N. tabacum. Four vectors, derived from Apple latent spherical virus (ALSV), Satellite tobacco mosaic virus (STMV), Tobacco rattle virus (TRV), and 2mDNA1 with TYLCCNV, were reported to be functional in the N. tabacum plant (Gossele et al, 2002;Ryu et al, 2004;Huang et al, 2009;Igarashi et al, 2009). However, their use has been limited by the difficulties encountered in gene delivery to N. tabacum plants.…”
Section: Discussionmentioning
confidence: 99%